Hypoxic preconditioning enhances neural stem cell transplantation therapy after intracerebral hemorrhage in mice. Issue 12 (December 2016) - Wakai, Takuma; Narasimhan, Purnima; Sakata, Hiroyuki; Wang, Eric; Yoshioka, Hideyuki; Kinouchi, Hiroyuki; Chan, Pak H
Previous studies have shown that intraparenchymal transplantation of neural stem cells ameliorates neurological deficits in animals with intracerebral hemorrhage. However, hemoglobin in the host brain environment causes massive grafted cell death and reduces the effectiveness of this approach. Several studies have shown that preconditioning induced by sublethal hypoxia can markedly improve the tolerance of treated subjects to more severe insults. Therefore, we investigated whether hypoxic preconditioning enhances neural stem cell resilience to the hemorrhagic stroke environment and improves therapeutic effects in mice. To assess whether hypoxic preconditioning enhances neural stem cell survival when exposed to hemoglobin, neural stem cells were exposed to 5% hypoxia for 24 hours before exposure to hemoglobin. To study the effectiveness of hypoxic preconditioning on grafted-neural stem cell recovery, neural stem cells subjected to hypoxic preconditioning were grafted into the parenchyma 3 days after intracerebral hemorrhage. Hypoxic preconditioning significantly enhanced viability of the neural stem cells exposed to hemoglobin and increased grafted-cell survival in the intracerebral hemorrhage brain. Hypoxic preconditioning also increased neural stem cell secretion of vascular endothelial growth factor. Finally, transplanted neural stem cells with hypoxic preconditioning exhibited enhanced tissue-protective capability that accelerated behavioral recovery. Our results suggest that hypoxic preconditioning in neural stem cells improves efficacy of stem cell therapy for intracerebral hemorrhage.